Dual Band Printed Bow-Tie Antenna For WLAN/WIMAX Application - Vijay, S. K.; Hassan, Nornikman; Ahmad, Mohd Riduan; Ahmad, Badrul Hisham; Rawat, Sanyog; Ray, Kanad (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
In this paper a dual band printed bow-tie antenna for WLAN and WiMAX application has been presented. A planar bow tie antenna consists of defected ground and symmetrical shape split ring resonator (SRR) is presented to apply to the dual band application. A triangular microstrip patch with the defected ground is used as initial bow tie antenna which worked on WiMAX Band. Further initial design (primary antenna) added with SRR to operate over 2.4-2.8 GHz for Bluetooth, Wi-Fi, ZigBee, WLAN Applications and 3.4-4.2 GHz which includes Worldwide Interoperability for Microwave Access (WiMAX) and C-band down link frequency band for satellite communications. The proposed antenna has been made on 1.6 mm thick FR-4 substrate with a size of 50x28 mm2. The proposed antenna has very wide bandwidth with the value of VSWR less than 2.